Exploring Smoking Influences on Asian Children and Adolescents: A Scoping Review - Novitasari, Nita Dewi; Shaluhiyah, Zahroh; Suryoputro, Antono (Universitas Airlangga, 2026)
Background: Smoking is a leading cause of non-communicable diseases and remains a significant public health challenge, particularly among children and adolescents in Asia, where prevalence rates are high. This behavior is influenced by a complex interplay of individual traits, interpersonal relationships, and broader social-environmental factors. Understanding these influences is crucial for developing effective interventions to reduce smoking among youth. Objectives: This study aimed to identify and map the key factors influencing smoking behavior among Asian children and adolescents, providing insights into potential strategies for targeted interventions. Methods: A scoping review was conducted through systematic searches of the Scopus and ScienceDirect databases using keywords related to smoking among Asian youth. From an initial pool of 312 articles, four met the inclusion criteria for in-depth analysis. Thematic analysis categorized influencing factors into individual, interpersonal, and socio-environmental domains. Results: The review identified three main categories of factors. Individual factors included age, gender, and curiosity, which often trigger initial smoking. Interpersonal influences such as peer pressure and family members who smoke played a significant role. Social and environmental factors, including exposure to tobacco advertising, easy access to cigarettes, and weak regulatory frameworks, further increased smoking risks. These factors frequently interacted, compounding their impact on youth smoking behaviors. Conclusion: Addressing smoking among Asian youth requires comprehensive strategies that encompass education, regulation, and family involvement. School-based programs, social media campaigns, stricter laws, and family-focused interventions are essential to reduce smoking prevalence and foster healthier generations.